1996
DOI: 10.1136/hrt.76.5.397
|View full text |Cite
|
Sign up to set email alerts
|

How epicardial U-wave changes are reflected in body surface precordial electrocardiograms in anterior or inferoposterior myocardial ischaemia during coronary angioplasty.

Abstract: Objectives-To examine the epicardial Uwave changes recorded in intracoronary electrocardigrams (ECGs) (Heart 1996;76:397-405)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…A resting negative U wave may indicate the presence of heart disease due to hypertension, valvular disease, and chronic ischemia 14 . Changes in the intracoronary U wave during ischemia were more readily detected by the IC‐ECG than by the S‐ECG 15, 16 . Further, it was suggested that the nature of intracoronary U‐wave change during ischemia may distinguish between acute or chronic ischemia 17 .…”
Section: Morphology Of the Intracoronary Electrocardiogrammentioning
confidence: 99%
See 2 more Smart Citations
“…A resting negative U wave may indicate the presence of heart disease due to hypertension, valvular disease, and chronic ischemia 14 . Changes in the intracoronary U wave during ischemia were more readily detected by the IC‐ECG than by the S‐ECG 15, 16 . Further, it was suggested that the nature of intracoronary U‐wave change during ischemia may distinguish between acute or chronic ischemia 17 .…”
Section: Morphology Of the Intracoronary Electrocardiogrammentioning
confidence: 99%
“…Further, it was suggested that the nature of intracoronary U‐wave change during ischemia may distinguish between acute or chronic ischemia 17 . The interpretation of the U wave on the IC‐ECG is complicated by the nonhomogeneity of U‐wave changes over a given area of myocardium, and the localized sampling of the IC‐ECG relative to the S‐ECG 15 . Further studies are needed, as discriminating between diseased and nondiseased myocardium by U‐wave morphology could help prioritize interventions during coronary angioplasty.…”
Section: Morphology Of the Intracoronary Electrocardiogrammentioning
confidence: 99%
See 1 more Smart Citation